Epidemiology of nosocomial colonization/infection caused by Acinetobacter spp. in patients of six surgical clinics in war and peacetime - Šuljagić Vesna; Jevtić Miodrag; Đorđević Boban; Romić Predrag; Ilić Radoje; Stanković Nebojša; Milović Novak; Novaković Marijan; Kozarski Jefta; Roganović Zoran; Popović Zoran; Jovelić Aleksandra (Vojnosanitetski Pregled)
Background/Aim. Acinetobacter spp. has emerged as nosocomial pathogen during the past few decades in hospitals all over the world, but it has increasingly been implicated as a serious nosocomial pathogen in military hospitals. The aim of this study was to analyze and compare the surveillance data on Acinetobacter nosocomial colonization/infection (NCI) collected during the wartime with the data collected in peacetime. Methods. We conducted a prospective study of incidence of Acinetobacter spp. colonization/ infection. Also, the two nested case-control studies were conducted. The patients with nosocomial infection (cases) were compared with those with nosocomial colonization (controls) during the two different periods, wartime and peacetime. The patients with NCI by Acinetobacter spp. were identified by the case-based surveillance. The surveillance covered all the patients in 6 surgical clinics. Results. During the study periods a total of 166 patients had cultures that grew Acinetobacter spp. and the pooled rates of Acinetobacter spp. colonization and infection were significantly higher in wartime. When patients with NCI in wartime were compared with those with NCI in peacetime significant differences were observed. In the war year, the patients were more significantly males (p < 0.000). In a period of peace, most of the colonization/infections were reported from patients with certain chronic diseases (p = 0.020) and the survival of patients was more significant (p = 0.049). During the peacetime, proportions of Acinetobacter isolates resistent to ciprofloksacin, imipenem and meropenem were significantly higher (p < 0.001). Conclusion. This study provides additional important information about the risk factors of nosocomial Acinetobacter spp. infections in a large cohort of surgical patients. This is also the first study that directly examines epidemiological differences between NCI caused by Acinetobacter spp. during the war and peace period.